PERLAKUAN BENIH DAN PEMUPUKAN TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) TSH 858 - Alridiwirsah ,; Asritanarni Munar; Fitri Anggun Sari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractThe study aims to evaluate the growth response of cocoa seedlings by stripping the pulp and seed husks in cocoa and Bayfolan fertilizer. The design used was factorial randomized block design with two factors were studied, namely: Seed Treatment Factor (K) consists of three levels, ie K1 = stripping lime pulp with water immersion, K2 = stripping pulp by rubbing ashes, K3 = partial stripping of the epidermis, and the provision of fertilizer Bayfolan factor (B) is divided into three levels, namely B1 = 2 ml / liter of water, B2 = 3 ml / liter of water, and B3 = 4 ml / liter of water. While the parameters measured were plant height, leaf number, stem diameter, leaf area, wet weight and wet weight on the bottom. The results showed that seed treatment showed a marked influence on plant height parameters ages 4, 6, 8 and 10 weeks after moving planting (MSPT), the number of leaf age of 4, 6 and 8 MSPT, and stem diameter MSPT age 8, but did not differ parameter significant at age 10 MSPT leaf number, stem diameter ages 4, 6 and 10 MSPT, leaf area, as well as wet weight. While the treatment of fertilizer Bayfolan showed different effects are not real at all parameter above observations. In the interaction shows a significantly different effect on the parameters of high-cocoa seedlings MSPT age 10, but not significant different in other observational parameters.Keywords: cocoa seedling, growth response,bayfolan, Theobroma cacao L.